Using artificial intelligence in chemistry and biology: practical guide - Cartwright, Hugh M. (CRC Press, 2020)
Table of Contents: Artificial Intelligence, Artificial Neural Networks, Self-Organizing Maps, Growing Cell Structures, Evolutionary Algorithms, Cellular Automata, Fuzzy Logic, Learning Classifier Systems, Evolvable Developmental Systems